2019
DOI: 10.1177/0361198118821925
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment Model for Railway Passengers on a Crowded Platform

Abstract: The purpose of this study is to develop a risk assessment measure to provide an understanding of the safety of railway station platforms. We estimated the number of accidents on a platform in a year. It was influenced by the factors such as the design, equipment, and the profile of the station users. Consequently, 16 factors were defined, such as the platform design and passenger movement. Poisson regression and negative binomial regression models were employed to estimate and analyze the number of accidents f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…If the railway sections approaching the trains are equipped with a semi-autoblocking system, in this case, the system that transmits the message about the approaching trains to the creatures, the noise generator is activated at the contact of the track relay of the rail chain or track sensors at the same distance from the point where the creatures gather in the even and odd directions [15][16][17][18][19][20][21][22][23][24].…”
Section: Algorithm Of Operation Of the System Of Transmission Of A Wa...mentioning
confidence: 99%
“…If the railway sections approaching the trains are equipped with a semi-autoblocking system, in this case, the system that transmits the message about the approaching trains to the creatures, the noise generator is activated at the contact of the track relay of the rail chain or track sensors at the same distance from the point where the creatures gather in the even and odd directions [15][16][17][18][19][20][21][22][23][24].…”
Section: Algorithm Of Operation Of the System Of Transmission Of A Wa...mentioning
confidence: 99%
“…For example, In Japan in 2016, 420 accidents occurred that included being struck by a train, which resulted in 202 deaths. This including of those 420 accidents, 179 (resulting in 24 fatalities) included falling from a platform and following injury or death as a consequence of hitting with a train [1]. In the UK, 2019/20, it has been reported that Most passenger injuries occur from accidents in stations.…”
Section: Introductionmentioning
confidence: 99%